Subjective cognitive Complaints in early Parkinson's disease patients with normal cognition are associated with affective symptoms. (January 2021) - Chua, Cong Yang; Koh, Matthew Rui En; Chia, Nicole Shuang-Yu; Ng, Samuel Yong-Ern; Saffari, Seyed Ehsan; Wen, Ming-Ching; Chen, Regina Yu-Ying; Choi, Xinyi; Heng, Dede Liana; Neo, Shermyn Xiumin; Tay, Kay Yaw; Au, Wing Lok; et al.
Abstract: Introduction: Subjective cognitive complaints (SCC) and affective symptoms are highly prevalent in Parkinson's Disease (PD). In early PD, SCC prevalence and its affective correlates, using recommended Movement Disorders Society (MDS) Level II Criteria to define the underlying cognitive impairment, has not been previously explored. Methods: We recruited 121 participants with early PD from two tertiary hospitals in Singapore. The presence of SCC was defined using a Non-Motor Symptoms Scale Domain-5 Score ≥1. Comprehensive neuropsychological testing was conducted with Mild Cognitive Impairment (PD-MCI) defined using recommended MDS Level II Criteria. Affective symptoms were assessed using the Hospital Anxiety Depression Scale (HADS), Geriatric Depression Scale (GDS) and Apathy Scale (AS). Analysis using multivariable linear regression model was performed. Results: In our early PD cohort, SCC prevalence independent of underlying cognitive status was 38.8%. Prevalence of SCC in cognitively impaired and cognitively normal participants was 10.7% and 28.1% respectively ( р  = 0.241). In cognitively normal PD participants, multivariable linear regression analysis revealed that SCC was significantly associated with anxiety (β = 0.28, 95% CI = 0.09–0.79, p  = 0.014), depression (β = 0.31, 95% CI = 0.10–0.59, p  = 0.006) and apathy (β = 0.32, 95% CI = 1.15–5.98, p  = 0.004). Such an association was not found in cognitively impaired PD participants. Conclusion: SCC is highly prevalent even in early PD. Its implications in early PD differ depending on underlying cognitive status. SCC in cognitively impaired participants underestimates the true prevalence of PD-MCI. In contrast, SCC in cognitively normal participants is suggestive of an underlying affective disorder. Highlights: We assessed subjective cognitive complaints (SCC) and its affective correlates in an early PD cohort. Mild cognitive impairment (MCI) was defined using recommended MDS Level II Diagnostic Criteria. SCC is highly prevalent (38.8%) even in early PD. In cognitively impaired early PD participants, SCCs underestimates true MCI prevalence. SCC in cognitively normal early PD participants are suggestive of an underlying affective disorder.